2011
DOI: 10.1007/s13197-011-0447-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on antioxidant activities of extracts and fractions from the leaves and stem of Epimedium koreanum Nakai

Abstract: The antioxidant potency of various extracts and fractions from the leaves and stem of Epimedium koreanum Nakai was evaluated using three esteblished methods, specifically the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radica-scavenging activity assay, the inhibitory effect on lipid peroxidation induced by Fe 2+ /ascorbate (MDA) assay and the ferric reducing power (FRP) assay. The amounts of total phenolics and total flavonoids in the extracts and fractions were determined by spectrophotometric methods and the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Our previous study reported that decursin acted to improve sperm count and motility by increasing antioxidant activity and decreasing apoptosis in patients with male infertility [12]. Li et al [11] reported that decursin may be able to prevent chemotherapy-induced cytotoxicity via the activation of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study reported that decursin acted to improve sperm count and motility by increasing antioxidant activity and decreasing apoptosis in patients with male infertility [12]. Li et al [11] reported that decursin may be able to prevent chemotherapy-induced cytotoxicity via the activation of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, decursin, a major active component of Angelica gigas Nakai, has demonstrated a cellular antioxidant defense capacity through free radical scavenging activity in cryptorchidism-induced male infertility [1011]. Icariin, contained in Epimedium koreanum Nakai, has shown some antioxidant effects, including a reduction of free radicals and lipid peroxidation inhibition [12], and has been found to improve erectile function in aged rats [13]. These results suggest that these herbal compounds have a safe and positive influence on sperm quality and on sexual behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of ferric reducing power was a commonly used model to study the antioxidant property of natural product extracts . Reducing capacity ( A 700 nm ) of WP and WPH increased with the increase of concentrations (0.01–0.06 g L −1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al (27) examined the antioxidant activity of parsley essential oil by DPPH method. The IC 50 value of this essential oil was very high (21.80 mg/mL), indicating a very poor antioxidant activity of the essential oil (27). Kamkar (28), reported the oxidation prevention power of linoleic acid in ethanolic extract of Iranian Anethum graveloens at a concentration of 2 g/L as 56%.…”
Section: Discussionmentioning
confidence: 99%